The Potential of Purun Plants as a Source for Learning Biology - Sri Mulyani; Raudhatul Fadhilah; Mahwar Qurbaniah (Postgraduate, University of Mataram, 2025)
West Kalimantan has different types of wetlands spread across highland and lowland areas , including rivers, swamps, coasts, mangrove forests, lakes, ponds, reservoirs, and paddy. One of these areas is Mempawah Regency, which is the habitat of various aquatic plants. One of the prominent species in this area is Purun, a type of weed from the Cyperaceae family. This study explores the potential of Purun plants as a source of contextual learning and its use by the community in Segedong District. The method used is qualitative descriptive, with data collection techniques through observation, interviews, identification, documentation, and questionnaires to teachers. This study identified two types of Purun, namely the rat Purun (Eleocharis dulcis) and the lake Purun (Lepironia articulata), which are used by residents in two villages to making craft products. This plant has great potential to be integrated into the junior high school biology curriculum, particularly in biodiversity, classification, and ecology materials. The results of the evaluation showed a positive perception of Purun as a learning resource: clarity of potential (72.91%), clarity of goals (66.66%), clarity of purpose (70.83%), clarity of information (68.75%), exploration clarity (75%), and yield clarity (70.83%).